2018
DOI: 10.1136/bmj.k4067
|View full text |Cite|
|
Sign up to set email alerts
|

Serial circulating omega 3 polyunsaturated fatty acids and healthy ageing among older adults in the Cardiovascular Health Study: prospective cohort study

Abstract: ObjectiveTo determine the longitudinal association between serial biomarker measures of circulating omega 3 polyunsaturated fatty acid (n3-PUFA) levels and healthy ageing.DesignProspective cohort study.SettingFour communities in the United States (Cardiovascular Health Study) from 1992 to 2015.Participants2622 adults with a mean (SD) age of 74.4 (4.8) and with successful healthy ageing at baseline in 1992-93.ExposureCumulative levels of plasma phospholipid n3-PUFAs were measured using gas chromatography in 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 73 publications
2
36
0
Order By: Relevance
“…Mainly found in fish oils, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are marine n-3 polyunsaturated fatty acids (PUFAs) involved in human physiology; received increasing attention in recent years due to its wide range of biological activities. Some studies showed that n-3 PUFAs may reduce the risk of CHD, ischemic stroke, alleviate inflammation and promote healthier cognitive aging [4][5][6][7][8][9]. For the past few years, animal and cell culture studies have demonstrated that n-3 PUFAs also have beneficial effects on prevention of T2DM through multiple mechanisms including insulin signaling, antiinflammatory actions, altering cell membrane function, and control the expression of glucose metabolism genes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Mainly found in fish oils, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are marine n-3 polyunsaturated fatty acids (PUFAs) involved in human physiology; received increasing attention in recent years due to its wide range of biological activities. Some studies showed that n-3 PUFAs may reduce the risk of CHD, ischemic stroke, alleviate inflammation and promote healthier cognitive aging [4][5][6][7][8][9]. For the past few years, animal and cell culture studies have demonstrated that n-3 PUFAs also have beneficial effects on prevention of T2DM through multiple mechanisms including insulin signaling, antiinflammatory actions, altering cell membrane function, and control the expression of glucose metabolism genes [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a linked paper in this issue, Lai and colleagues (doi: 10.1136/bmj.k4067 ) investigate the association between circulating levels of omega 3 polyunsaturated fatty acids (n3-PUFAs) and healthy ageing in a sample of adults with a mean age of 74 years at baseline who were followed for up to 22 years in the Cardiovascular Health Study. 5 Among the 5888 participants enrolled from Medicare (aged 65 or more or receiving social security disability insurance) at four communities in the United States, 2622 eligible participants were included in this analysis.…”
mentioning
confidence: 99%
“…PUFA accounted for a large proportion of total lipids. n-3 and n-6 PUFA, which help prevent several diseases, especially cardiovascular conditions [2,3,39], accounted for 35-40% of total lipids. As previous studies confirmed [7][8][9], a diet providing large amounts of these fats is therefore recommended especially during childhood [12,13].…”
Section: Discussionmentioning
confidence: 99%